From Semi-Axes Sum to Conjugate Semi-Diameters

Geometry Level 4

Consider the ellipse described by

r ( t ) = C + f 1 cos t + f 2 sin t \mathbf{r}(t) = \mathbf{C} + \mathbf{f_1} \cos t + \mathbf{f_2} \sin t

The vectors f 1 , f 2 \mathbf{f_1} , \mathbf{f_2} are a pair of conjugate semi-diameters of this ellipse.

Now, suppose you are given that f 1 = ( 7 , 10 ) \mathbf{f_1} = (7, 10) and f 2 = ( 3 , n ) \mathbf{f_2} = (3, n) for a positive integer n n , and that the sum of the semi-axes lengths of this ellipse is 25 25 .

Find n n .

Inspiration


The answer is 17.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hosam Hajjir
Jul 15, 2020

Re-arranging the given vector equation using the unit vector u = [ cos t , sin t ] T \mathbf{u} = [ \cos t , \sin t ]^T , we have,

r C = F u \mathbf{r} - \mathbf{C} = \mathbf{F} \mathbf{u}

where the columns of matrix F \mathbf{F} are the vectors f 1 \mathbf{f_1} and f 2 \mathbf{f_2} .

Now, since u T u = 1 \mathbf{u}^T \mathbf{u} = 1 , the above vector equation becomes the algebraic equation,

( r C ) T F T F 1 ( r C ) = 1 (\mathbf{r} - \mathbf{C})^T \mathbf{F}^{-T} \mathbf{F}^{-1} (\mathbf{r} - \mathbf{C}) = 1

It follows that the eigenvalues of the inverse of the matrix F T F 1 \mathbf{F}^{-T} \mathbf{F}^{-1} , which is the matrix F F T \mathbf{F} \mathbf{F}^T are a 2 a^2 and b 2 b^2 .

F F T = [ 7 3 10 n ] [ 7 10 3 n ] = [ 58 70 + 3 n 70 + 3 n 100 + n 2 ] \mathbf{F} \mathbf{F}^T = \begin{bmatrix} 7 && 3 \\ 10 && n \end{bmatrix} \begin{bmatrix} 7 && 10 \\ 3 && n \end{bmatrix} = \begin{bmatrix} 58 && 70+3n \\ 70+3n && 100+n^2 \end{bmatrix}

The characteristic equation of this matrix is ( λ 58 ) ( λ ( 100 + n 2 ) ) ( 70 + 3 n ) 2 = 0 (\lambda - 58)(\lambda - (100+n^2) ) - (70+3n)^2 = 0

Since the two roots of this equation are a 2 a^2 and b 2 b^2 , then

a 2 + b 2 = 158 + n 2 a^2 + b^2 = 158 + n^2

and

a 2 b 2 = 58 ( 100 + n 2 ) ( 70 + 3 n ) 2 = 49 n 2 420 n + 900 a^2 b^2 = 58(100+n^2) - (70+3n)^2 = 49 n^2 - 420 n + 900

In addition, we are given that a + b = 25 a + b = 25 , hence,

( a + b ) 2 = a 2 + b 2 + 2 a b (a + b)^2 = a^2 + b^2 + 2 a b

Therefore,

625 = 158 + n 2 + 2 49 n 2 420 n + 900 625 = 158 + n^2 + 2 \sqrt{ 49 n^2 - 420 n + 900 }

Re-arranging this, we get

4 ( 49 n 2 420 n + 900 ) = ( 467 n 2 ) 2 4 ( 49 n^2 - 420 n + 900) = ( 467 - n^2 )^2

A quartic equation with four real roots, two of which are valid and these are 14.3541565 -14.3541565 , and 17 17 and two extraneous solutions which are 31 -31 , and 28.3541565 28.3541565 . Since we are given that n n is an integer, then the only solution is 17 \boxed{17}

We Bengalees have an old proverb : frying a fish in it's own fat . Doing the same here!

Following you, the semi-axes are given by

a , b = 1 2 f 1 x 2 + f 1 y 2 + f 2 x 2 + f 2 y 2 ± ( ( f 1 x f 2 y ) 2 + ( f 1 y + f 2 x ) 2 ) ( ( f 1 x + f 2 y ) 2 + ( f 1 y f 2 x ) 2 ) a, b=\dfrac {1}{\sqrt 2}\sqrt {f_{1x}^2+f_{1y}^2+f_{2x}^2+f_{2y}^2\pm \sqrt {\left ((f_{1x}-f_{2y})^2+(f_{1y}+f_{2x})^2\right )\left ((f_{1x}+f_{2y})^2+(f_{1y}-f_{2x})^2\right )}}

= 1 2 ( n 2 + 14 n + 98 ± n 2 14 n + 218 ) =\dfrac 12 \left (\sqrt {n^2+14n+98}\pm \sqrt {n^2-14n+218}\right )

a + b = n 2 + 14 n + 98 = 25 \implies a+b=\sqrt {n^2+14n+98}=25 (given)

n 2 + 14 n 527 = 0 \implies n^2+14n-527=0

The positive solution to this equation is n = 17 n=\boxed {17} .

Haha, easy-to- understand solution plus I remember this proverb very well.

Siddharth Chakravarty - 10 months, 4 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...